Modelování souvislostí mezi hrozbami - Roudný, Radim; Svoboda, Ondřej (Univerzita Pardubice, 2010)
The article shows approach to model of relationship between threats. Many algorithms of risk analysis ignore the interrelationship between the events. For the present world are typical increasing interdependences of critical infrastructures and between risk events. The article shows examples of model of relationship between threats.
Keywords: risk analysis; threats interdependences; system dynamics; Vensim PLE